Editorial: Healthcare management: challenges for improving performance and quality of patient services. - Herrera-Ballesteros, Juan; De-las-Heras-Rosas, Carlos Javier; Mota Veiga, Pedro (Frontiers, 2023)
In healthcare, institutions face constant challenges due to technological advances and increasing societal expectations, particularly in times of pandemic. Personnel management becomes essential in these critical circumstances. Within this context, human capital management challenges are diverse. The lack of qualified staff, the coordination of specialized multidisciplinary teams, and the management of factors such as stress, burnout, job dissatisfaction, and high turnover present themselves as key obstacles to meeting the high standards of performance and quality of patient care that society demands. This Research Topic of Frontiers in Psychology includes seven articles. These publications were carried out using qualitative and quantitative techniques and systematic reviews. As units of analysis, the published articles have used nursing staff (4 doc.), first-line managers (1 doc.), general practitioners (1 doc.), and emergency staff (1 doc.).
Keywords: Asistencia sanitaria - Gestión; Calidad de vida en el trabajo; Personal sanitario; Asistencia sanitaria - Evaluación; Healthcare management; Job satisfaction; Organizational commitment; Performance; Quality of patient care